Acanthomatous Ameloblastoma of Mandible in a Paediatric Patient - Narasimhan Malathi; G. V. V. Giri; Deepak A. Pandyan; Ramalingam Suganya; Harikrishnan Thamizhchelvan (Hindawi Limited, 2018)
Ameloblastoma is a slow-growing, benign odontogenic tumor derived from odontogenic epithelial components with a mature fibrous stroma. It is the second most common odontogenic neoplasm following odontome. Acanthomatous ameloblastoma histologically presents with squamous epithelial metaplastic transformation of odontogenic tissue. The present case report of a 12-year-old male exclusively elaborates the issues concerned with the aggressive nature of acanthomatous ameloblastoma (AA) which is a distinctive variant of ameloblastoma.